Acetylcholine and Butyrylcholine Esterase Inhibitory Potential of Newly Synthesized Halogenated Compounds: In Vitro, In Silico and MD Simulation - Yesilbag, Semanur; Raza, Muhammad Asam; Sandhu, Zeshan Ali; Farwa, Umme; Poyraz, Emine Berrin; Iqbal, Bushra; Dege, Necmi (Elsevier, 2025)
Schiff bases have numerous applications especially in the medicinal chemistry. Keeping in view their importance, two new compounds; (E)-2-(((4-bromo-2-(trifluoromethyl) E )-2-(((4-bromo-2-(trifluoromethyl) phenyl)imino)methyl)-4-nitrophenol (1) and (E)-3- E )-3- ((4-bromo-2-(trifluoromethyl)phenylimino) methyl)pyridin-2-amine (2) have been synthesized. These Schiff bases were characterized with modern spectral tools while precise structures were confirmed through XRD which revealed that compound 1 was monoclinic and compound 2 was orthorhombic. The synthesized compounds were further evaluated theoretically by applying density functional theory approach. Regression coefficient (R-2) was utilized to compare the different parameters between DFT and XRD data. Hirshfeld surface study was used to find out the different interactions between the atoms presented in the crystalline molecules. Online free tool was used against AChE and BChE for accomplishment of the molecular modeling study. The molecular dynamics simulation study was also conducted to check the binding mechanism of the most active compound on AChE. On the basis of the docking score and MD simulation, compound 1 depicted more inhibition potential. The in-vitro studies further confirmed that synthesized Schiff bases have potential to cure the Alzheimer disease by inhibiting enzymes related to this disease.
Islam, Mohammad Shahidul/0000-0002-4612-5875; Raza, Muhammad/0000-0002-6723-2637; N, Dege/0000-0003-0660-4721; Iqbal, Bushra/0000-0001-6190-1812;
Keywords: Molecular Modeling; Acetylcholine and Butyrylcholine Esterase; Halogen Containing Compounds; MD Simulations; XRD Analysis; Density Functional Theory